Blood donations and incentives: evidence from a field experiment - Lorenz Götte; Alois Stutzer (Institute for the Study of Labor (IZA), 2008)
There is a longstanding concern that material incentives might undermine prosocial motivation, leading to a decrease in blood donations rather than an increase. This paper provides an empirical test of how material incentives affect blood donations in a large-scale field experiment spanning three months and involving more than 10,000 previous donors. We examine two types of incentive: a lottery ticket and a free cholesterol test. Lottery tickets significantly increase donations, in particular among less motivated donors. The cholesterol test leads to no discernable impact on usable blood donations. If anything, it creates a small negative selection effect in terms of donations that must be discarded.
urn:nbn:de:101:1-2008071153
Keywords: C93; 330; Prosocial behavior; blood donations; material incentives : field experiment; Blutspende; Soziales Verhalten; Ökonomischer Anreiz; Test